Integrated management of malnutrition in children under 5 - Manual for health care provider - Chin, Choy Nyok; Adnan, Suryati; Abdullah, Azmi; Chia, Kelvin Cheong Yung; Hassan, Rahimi; Wan Muhammad, Wan Abdul Rahim; Sulong, Mohd Rahim; Kamaruzaman, Nor Azam; Osman, Iskandar Firzada; Abdul Rahman, Abdul Khalek; Mohd Nording, Zahariah; Mohd Irani, Har Rasyidah; et al. (2015)
This manual was developed in 2015 aiming to guide health care provider specifically in Pahang on how to manage malnutrition case effectively. It consists of outpatient and inpatient guidelines.